Preferred orientation in deformed metals and rocks : an introduction to modern texture analysis - Wenk, Hans-Rudolf, 1941- (Academic Press, 1985)
This volume provides an introduction to the texture analysis of deformed materials and explores methods of determining and interpreting the preferred orientation of crystals in deformed polycrystalline aggregates.**The book reviews: 1) the techniques, procedures, and theoretical basis for the accumulation and analysis of orientation data; 2)the processes by which polycrystals deform and the microstructural mechanisms responsible for the development of the preferred orientation; 3) the textures in specific systems and application of principles to the solution of specific problems.**With a combi.